Unraveling the role of chemokines in cutaneous T-cell lymphoma: expression levels at different stages - Guglielmo, Alba; Zengarini, Corrado; Tugnoli, Federica; Zinzani, Pier Luigi; Borghi, Alessandro; Corazza, Monica; La Placa, Michelangelo; Piraccini, Bianca Maria; Pileri, Alessandro (Frontiers in Immunology, 2025)
Mycosis fungoides (MF) and Sezary syndrome (SS) are the most prevalent cutaneous T-cell lymphomas, classified separately in the 2022 WHO Classification due to their distinct features. Despite advances, the mechanisms underlying disease progression—from early patch and plaque lesions to advanced tumor stages—remain incompletely understood. Chemokines and their receptors play crucial roles in the migration and survival of malignant T cells, influencing tissue invasion, immune evasion, and dissemination. This review highlights the altered expression of chemokine receptors like CCR4, CCR7, CCR8, CCR10, CXCR3, and CXCR4 in MF/SS and their contribution to disease evolution. It also explores the transition from a Th1 to a Th2 immune profile, linked to tumor progression. The dual role of chemokines in physiology and pathology is examined, with emphasis on their therapeutic potential in CTCL.